Investigating teacher beliefs and attitudes on implementing mastery maths with interpretive phenomenological analysis - Suzanne McDonald (University of Aberdeen, School of Education, 2022)
This study investigates the potential influence of teachers' beliefs and attitudes when implementing a new mathematical reform. Mastery maths has been rolled out across local authorities in Scotland. Originally derived from an Asian method of teaching mathematics, it was favoured following Singapore's poor performance in the subject, particularly in the league tables of the 1980s. Interpretive Phenomenological Analysis (IPA) was adopted to gain a deeper understanding of the teachers' reality influencing beliefs and attitudes around the reform. Four primary school teachers were interviewed. The transcribed interviews revealed three general themes influencing the implementation: confidence, pedagogical understanding and teaching environment. The reform was overshadowed by misconception and future consideration is suggested to focus on precursory growth mindset training and transformative CPD before introducing a mathematical concept from a different culture.